Analisis 1D – 2D Genangan Banjir pada Kawasan Perumahan Baturaja Permai, Kecamatan Baturaja Timur - Rudy Suryadi; Dinar Dwi Anugerah Putranto; Imroatul C. Juliana (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2022)
Flooding is a problem that is often found in cities, especially in the rural areas of Baturaja Permai. When it rains, the quantity of river water exceeds its capacity or becomes too much, and there will be inundation caused by overflowing rivers. Factors of natural events such as high rainfall intensity cause flooding, coupled with factors from human activities. This study aims to investigate flood characteristics by developing an integrated model between hydrology and hydraulics. The development of this flood model is based on the hydrological model of runoff using the synthetic unit hydrograph method Soil Conservation Service (SCS), a one-dimensional (1D) hydraulic model for water flow propagation in macro drainage systems, and two dimensions (2D) for calculations if the river flow exceeds the existing capacity so that it experiences water propagation in the inundation area using the HEC-RAS software. To model the flood inundation it is required data Digital Elevation Model (DEM) was obtained by measuring the height of the land using a Total Station (TS) measuring instrument and analyzed using ArcMap software. The calculation of direct runoff is designed for a 5-year return period. The simulation results indicate that the Baturaja Permai area is an area that is prone to flooding with inundation depth of 0.558 m - 4.692 m and a peak runoff discharge of 15.6 m³/s at a 5-year return period.